Acute and chronic changes in brain activity with deep brain stimulation for refractory depression. (April 2018) - Conen, Silke; Matthews, Julian C; Patel, Nikunj K; Anton-Rodriguez, José; Talbot, Peter S
Deep brain stimulation is a potential option for patients with treatment-refractory depression. Deep brain stimulation benefits have been reported when targeting either the subgenual cingulate or ventral anterior capsule/nucleus accumbens. However, not all patients respond and optimum stimulation-site is uncertain. We compared deep brain stimulation of the subgenual cingulate and ventral anterior capsule/nucleus accumbens separately and combined in the same seven treatment-refractory depression patients, and investigated regional cerebral blood flow changes associated with acute and chronic deep brain stimulation. Deep brain stimulation-response was defined as reduction in Montgomery–Asberg Depression Rating Scale score from baseline of ≥50%, and remission as a Montgomery–Asberg Depression Rating Scale score ≤8. Changes in regional cerebral blood flow were assessed using [ 15 O]water positron emission tomography. Remitters had higher relative regional cerebral blood flow in the prefrontal cortex at baseline and all subsequent time-points compared to non-remitters and non-responders, with prefrontal cortex regional cerebral blood flow generally increasing with chronic deep brain stimulation. These effects were consistent regardless of stimulation-site. Overall, no significant regional cerebral blood flow changes were apparent when deep brain stimulation was acutely interrupted. Deep brain stimulation improved treatment-refractory depression severity in the majority of patients, with consistent changes in local and distant brain regions regardless of target stimulation. Remission of depression was reached in patients with higher baseline prefrontal regional cerebral blood flow. Because of the small sample size these results are preliminary and further evaluation is necessary to determine whether prefrontal cortex regional cerebral blood flow could be a predictive biomarker of treatment response.